Design of S/C/X/Ku frequency band five notch broadband filter based on novel coupled signal path - Guojin Li; Wenxian Yang; Jingchang Nan (PLoS ONE, 2025)
This article present the design of a broadband filter structure spanning the S, C, X, and Ku uplink bands based on a novel coupling signal path generation. The core design features a centrally symmetric serial via hole array, microstrip line, and curved coplanar waveguide. This structure offers advantages such as low loss band pass, low frequency stopband in the S band, and stable transmission zeros while providing a broadband passband. Additionally, to address the signal suppression requirements in commercial communication frequencies, such as 5G base stations, 6G IMT, satellite TV, and Starlink, across the S, C, X, and Ku uplink bands, a dual-band notch structure for the C band and three improved signal suppression structures are proposed. Finally, the design achieves miniaturization and integration while ensuring excellent performance across all five independent stopbands. Experimental results closely match simulation findings: the filter exhibits a –3 dB bandwidth of 2.4–14.3 GHz with a relative bandwidth of up to 141%. Each of the five suppression depths reaches –15 dB, occupying a compact footprint of only 14×10.8mm2,with a relative wave guide area of 0.38 × 0.29λ2.